The Dynamics of Police Leadership in Facing ‘No Viral, No Justice’ Phenomenon and the Challenges of Law Enforcement in the Digital Era - Aldhira Farhan Manurung; Surya Nita; Zora Arfina (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
With the development of digital technology emerges the ‘No Viral No Justice’ Phenomenon, wherein law enforcement is oftentimes influenced by the virality of a case in social media. The phenomenon gives new challenges for law enforcement institutions especially The Indonesian National Police (INP) which creates a new perspective of the legal process that runs effectively due to the public’s spotlight. This research aims to analyze the influence of this phenomenon on law enforcement by INP, the role of police leadership in managing public pressure and social media opinion, and strategic moves to increase transparency, accountability, and public trust. This research uses qualitative methods by focusing on viral case analysis. The research shows that ‘No Viral No Justice’ influenced the case handling priority, increasing transparency and accountability thanks to public surveillance, conversely emerging hasty investigation, manipulation of opinion, and disinformation. Thus, the INP’s leadership needed an effective strategy for public communication and adaptive crisis management. To increase public trust, the INP suggested strengthening open communication, applying an integrated reporting system, utilizing digital communication, creating a special unit for viral cases, and improving training and public collaboration.